2014
DOI: 10.1016/j.jcis.2013.11.040
|View full text |Cite
|
Sign up to set email alerts
|

A review of the removal of anions and oxyanions of the halogen elements from aqueous solution by layered double hydroxides

Abstract: The application of layered double hydroxides (LDHs) and thermally activated LDHs for the removal of various fluorine (F(-),BF4(-)), chlorine (Cl(-),ClO4(-)), bromine (Br(-),BrO3(-)) and iodine (I(-),IO3(-)) species from aqueous solutions has been reviewed in this article. LDHs and thermally activated LDHs were able to significantly reduce the concentration of selected anions in laboratory scale experiments. The M(2+):M(3+) cation ratio of the LDH adsorbent was an important factor which influenced anion uptake.… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
75
0

Year Published

2015
2015
2022
2022

Publication Types

Select...
5
1
1

Relationship

0
7

Authors

Journals

citations
Cited by 202 publications
(75 citation statements)
references
References 37 publications
0
75
0
Order By: Relevance
“…LDH has been demonstrated as a promising carrier for drug delivery, according to its expandable interlayer space, low cytotoxicity, and high biocompatibility 12, 13, 14, 15. Our team's previous research has already confirmed that layered double hydroxide loaded with etoposide (LDH‐VP16) is very effective in inhibiting A549 cell migration and invasion in vitro via the mTOR/AKT and STAT pathways 16.…”
Section: Introductionmentioning
confidence: 89%
“…LDH has been demonstrated as a promising carrier for drug delivery, according to its expandable interlayer space, low cytotoxicity, and high biocompatibility 12, 13, 14, 15. Our team's previous research has already confirmed that layered double hydroxide loaded with etoposide (LDH‐VP16) is very effective in inhibiting A549 cell migration and invasion in vitro via the mTOR/AKT and STAT pathways 16.…”
Section: Introductionmentioning
confidence: 89%
“…Many reports indicate high fluoride content exist in drinking water in many countries like China, Russia, Pakistan, South Africa [1][2][3]. Use of drinking water containing high concentration of fluoride can cuse dental fluorosis, nervous system diseases, and even cancer [4][5][6].…”
Section: Introductionmentioning
confidence: 99%
“…and have been regarded as effective adsorbent in reducing the contents of excessive anions, including fluoride [12,[16][17][18]. LDHs are composed of alternating stacked cationic layers and interlayer compensation anions.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…[17][18][19][20] There is an increasing attention for these materials owing to their several applications in many fields such as catalysis, removal of waste agents from water, stabilizers and rheology modifiers, preparation of pigments, pharmaceutical and cosmetic formulations, symptomatic treatment of peptic ulcer and therapy of digestive disorders, drug and biomolecule hosts, organic-inorganic NCs. [20][21][22][23][24][25][26][27][28][29][30] High-performance polymers are good candidates as matrices in NCs due to their excellent properties, namely high thermal stability, stiffness, flame retardancy, strength, thermo-oxidative stability, toughness, high conductivity, chemical and solvent resistance, low dielectric constant, retained properties at very high temperatures, and long storage periods. [31][32][33][34] Poly(amide-imide)s (PAI)s are one of the most successful classes of high-performance polymers.…”
Section: Introductionmentioning
confidence: 99%